Knowledge versus experience: indicator to good journalism practices - Awan Ismail,; Rizalawati Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Globally, journalism education is undergoing significant changes in view of the ongoing technological evolution. Hence, it is important to have a good journalism education that can shape good journalism practices and professionalism. In recognition of this, the Council for Heads of Communication Studies (COHEC) in Malaysia has mapped out a framework for journalism education to be offered by Malaysian universities (COHEC, 2010). However, COHEC study was very brief and did not underline what makes good journalism practice. Therefore, this study seeks to identify the knowledge, experience, and skills needed in Malaysian journalism education. To this end, this study conducted in-depth interviews with senior practitioners – senior editors and chief editors - from media organizations in Malaysia. Findings show the importance of knowledge, experience, skills, and attitude needed for good journalism practices. The findings also acknowledged that journalism knowledge is as important as experience and debunked the old testimony that knowledge can be practiced on the job and no formal journalism education is needed. The understanding of journalism is not as a skill but as social, cultural, and philosophical expression, and general education is needed to cover the journalistic aspect of life. There is a need to redefine journalism as a field of study.